2002
DOI: 10.1021/es010249w
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Depuration of 4-tert-Octylphenol Residues in the Cyprinid Fish, Scardinius erythrophthalmus

Abstract: Alkylphenols are present in the aquatic environment through the degradation of alkylphenolpolyethoxylate surfactants in sewage treatment works. Branched chain 4-alkylphenols have been shown to retard testicular growth and stimulate vitellogenin synthesis in freshwater fish. We conducted in vivo studies in order to determine the fate and persistence of radiolabeled 4-tert-octylphenol (tOP) in the cyprinid fish, rudd (Scardinius erythrophthalmus). Sexually mature rudd were exposed to a concentration of 4.7 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 64 publications
3
16
0
1
Order By: Relevance
“…These in situ BCF values of OP and NP in this field study were consistent with those reported by other investigators. The BCF values had been reported for NP (34 121) in roach bile and for t-OP in trout (56 000) (Smith and Hill, 2004) and rud (20 000) by Ferreira-Leach and Hill (2001) and Pedersen and Hill (2002). And these values were slightly lower than the EEQ BCF in the bile of fish exposed to sewage effluent reported by Tyler et al (2005).…”
Section: Bioaccumulation Factors For Edcs In Carp Bile and Algaementioning
confidence: 89%
See 1 more Smart Citation
“…These in situ BCF values of OP and NP in this field study were consistent with those reported by other investigators. The BCF values had been reported for NP (34 121) in roach bile and for t-OP in trout (56 000) (Smith and Hill, 2004) and rud (20 000) by Ferreira-Leach and Hill (2001) and Pedersen and Hill (2002). And these values were slightly lower than the EEQ BCF in the bile of fish exposed to sewage effluent reported by Tyler et al (2005).…”
Section: Bioaccumulation Factors For Edcs In Carp Bile and Algaementioning
confidence: 89%
“…Recent studies showed that http://dx.doi.org/10.1016/j.chemosphere.2014.01.048 0045-6535/Ó 2014 Elsevier Ltd. All rights reserved. numerous chemical substances, including estrogens and alkylphenols, tend to concentrate as glucuronide and sulfate conjugates in fish bile (Larsson et al, 1999;Ferreira-Leach and Hill, 2001;Legler et al, 2002;Pedersen and Hill, 2002). Moreover, analysis of fish bile, representative of recent exposure to bioavailable contaminants, was employed to identify and quantify polycyclic aromatic hydrocarbons (Ruddock et al, 2003;Johnson-Restrepo et al, 2008), chlorinated phenols (Brumley et al, 1998), resin, and fatty acids from pulp and paper mill effluents (Leppänen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Alkylphenol ethoxylates are used, among others, as nonionic surfactants in household and industrial detergents and reach the hydrosphere by household and industrial wastewater (Leisewitz et al 2003). Alkylphenol ethoxylates consisted until 2002 mainly of nonylphenol ethoxylates (80%) and octylphenol ethoxylates (15-20%; Pedersen and Hill 2002). Tech.…”
Section: Introductionmentioning
confidence: 99%
“…Bigarren erreakzioari 2. fasea (Phase II) deritzo. Han, metabolito berri horien -OH edo -COOH taldeei glukuronido [32][33][34], glukosido [35] edo sulfato [32] talde bat lotzen zaie, konposatu polarragoak lortuz; hartara, behazunaren bidez kanporatzeko errazagoak diren konposatuak bilakatuz. Konposatu polarragoak (eraldatu gabe -OH edo -COOH taldea daukatenek) ez dute 1. fasea pairatzen, eta zuzenean 2. fasean transformatzen dira.…”
Section: Gibelaunclassified